Análise das políticas e práticas da EJA, na Secretaria Municipal de Educação, no município de São Bernardo do Campo a partir da perspectiva freireana - Silva, Adriana Pereira da (2012)
This registration concerns a research that was carried out with the intention of analyzing the limits and possibilities that are faced by Adult Education in order to organize an integral formation that links education and work in a Freirean perspective, in which dialogue and participation are fundamental issues. In this regard, there was a bibliographic research that leaded to an analysis of some parts of the history of Adult Education in Brazil and its curricular organization with an analytic interpretation of which was the formative proposition on those ages. In continuity to the theoretic study, based on Freire, it was made a reflection about the formative possibilities that come to respect the human needs in its dimensions: ethics, esthetics and technique, and it was analyzed how a curriculum for Young and Adults can respond to those dimensions in a critic perspective, following the patterns of an integral formation. In order to enlighten the reflection, it was done a qualitative research. The field research occurred in two dimensions, there was a documental research about the normative of the Department of Education towards Adult Education with the purpose of understanding how the orientations influenced the practices and the curricular organization of that education network for this modality. Still during the field research there was the intention of verifying the limits and possibilities that the educative practice has to proceed with an integral formation in a Freirean perspective, so there was a study in two schools in which the information collected helped to understand the profile and the conceptions that educators and the administrators of those schools have about Adult Education. Besides, it was possible to realize how they organize the curriculum, leading to occur an observation of the didactic practice